Dirtying bank work: when taint is reinforced by the organisation. Issue 5 (3rd September 2022) - Carollo, Luca; Gilardi, Silvia
ABSTRACT: While researchers have to date mainly focused on the coping strategies employed by dirty workers to normalise taint, the organisational and managerial roots of dirty work have been little explored. The article contributes to filling this gap by means of a single case study conducted in a big Italian banking company. In the research context investigated, branch-level bank employees felt themselves tainted from the moral (as 'vendors') and social (as 'servants of customers') points of view. These perceptions were directly associated with organisational strategies and managerial practices intended to fulfil demanding sales targets or to create more space and freedom for customers. Although the literature assumes that occupational taint is generated by external societal attributions, by introducing the concept of 'organisationally-reinforced taint' this study shows that internal organisational strategies and managerial practices can contribute to dirtying an occupation, even a relatively prestigious one like bank work.